2015
DOI: 10.1016/j.yexcr.2015.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-(1–7) counteracts angiotensin II-induced dysfunction in cerebral endothelial cells via modulating Nox2/ROS and PI3K/NO pathways

Abstract: Angiotensin (Ang) II, the main effector of the renin-angiotensin system, has been implicated in the pathogenesis of vascular diseases. Ang-(1-7) binds to the G protein-coupled Mas receptor (MasR) and can exert vasoprotective effects. We investigated the effects and underlying mechanisms of Ang-(1-7) on Ang II-induced dysfunction and oxidative stress in human brain microvascular endothelial cells (HbmECs). The pro-apoptotic activity, reactive oxygen species (ROS) and nitric oxide (NO) productions in HbmECs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
46
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 54 publications
7
46
1
Order By: Relevance
“…Upstream of NF-κB, Ang-(1-7) promoted the inhibition of NADPH oxidase and diminished ROS generation, which in turn led to a marked attenuation of the NF-κB/iNOS axis and thus of human VSMC activation ( Figure 5 ). This is in line with other reports showing that Ang-(1-7) negatively regulates NADPH oxidase activation elicited by Ang II in endothelial cells (Sampaio et al, 2007; Xiao et al, 2015) or other non-vascular cell types, such as skeletal muscle or kidney tubular cells, among other (Kim et al, 2012; Morales et al, 2014). The activation of the IP3/Akt pathway, one of most relevant Mas-related signaling events acknowledged to date (Bader et al, 2014), might be on the basis of the protective effect of Ang-(1-7) against NOX-derived ROS formation and apoptosis in cerebral endothelial cells (Xiao et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Upstream of NF-κB, Ang-(1-7) promoted the inhibition of NADPH oxidase and diminished ROS generation, which in turn led to a marked attenuation of the NF-κB/iNOS axis and thus of human VSMC activation ( Figure 5 ). This is in line with other reports showing that Ang-(1-7) negatively regulates NADPH oxidase activation elicited by Ang II in endothelial cells (Sampaio et al, 2007; Xiao et al, 2015) or other non-vascular cell types, such as skeletal muscle or kidney tubular cells, among other (Kim et al, 2012; Morales et al, 2014). The activation of the IP3/Akt pathway, one of most relevant Mas-related signaling events acknowledged to date (Bader et al, 2014), might be on the basis of the protective effect of Ang-(1-7) against NOX-derived ROS formation and apoptosis in cerebral endothelial cells (Xiao et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…This is in line with other reports showing that Ang-(1-7) negatively regulates NADPH oxidase activation elicited by Ang II in endothelial cells (Sampaio et al, 2007; Xiao et al, 2015) or other non-vascular cell types, such as skeletal muscle or kidney tubular cells, among other (Kim et al, 2012; Morales et al, 2014). The activation of the IP3/Akt pathway, one of most relevant Mas-related signaling events acknowledged to date (Bader et al, 2014), might be on the basis of the protective effect of Ang-(1-7) against NOX-derived ROS formation and apoptosis in cerebral endothelial cells (Xiao et al, 2015). In embryonic pancreatic explants, however, Ang-(1-7) rather seems to activate NADPH oxidase (Wang et al, 2015), which indicates that the precise mechanisms linking Mas activation and NADPH oxidase activity may be complex and still remain to be explored more in depth.…”
Section: Discussionsupporting
confidence: 93%
“…Based on these data, we suggest that NF-κB signaling is the major target of melatonin to modulate BBB function caused by METH. However, the inhibition of NF-κB did not completely decrease the ROS level, which was mostly generated by NOX2 (Park et al, 2012;GarridoUrbani et al, 2014;Xiao et al, 2015). Thus, the inhibition of NF-κB was not the only critical factor in the protection of the BBB.…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated that Ang-(1-7)/Mas axis prevented the rise of ROS levels induced by TGF-β1 in C 2 C 12 myotubes. These results concur with previous evidence indicating that Ang-(1-7) via the Mas receptor decreases oxidative stress in different cell types, such as adipocytes [49], cerebral endothelial cells [50], and, interestingly, in pathologies associated with skeletal muscle atrophy such as diabetes [51], cardiac failure [52], and hepatic damage [53]. Additionally, previously published results by us shows that Ang-(1-7)/Mas receptor prevents ROS induction by Ang-II in skeletal muscle cells [54].…”
Section: Discussionsupporting
confidence: 93%